Fear of failure, psychological stress, and burnout among adolescent athletes competing in high level sport - Gustafsson, H.; Sagar, S. S.; Stenling, A. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The purpose of this study was to investigate fear of failure in highly competitive junior athletes and the association with psychological stress and burnout. In total 258 athletes (152 males and 108 females) ranged in age from 15 to 19 years (M = 17.4 years, SD = 1.08) participated. Athletes competed in variety of sports including both team and individual sports. Results showed in a variable-oriented approach using regression analyses that one dimension, fear of experiencing shame and embarrassment had a statistically significant effect on perceived psychological stress and one dimension of burnout, reduced sense of accomplishment. However, adopting a person-oriented approach using latent class analysis, we found that athletes with high levels of fear failure on all dimensions scored high on burnout. We also found another class with high scores on burnout. These athletes had high scores on the individual-oriented dimensions of fear of failure and low scores on the other oriented fear of failure dimensions. The findings indicate that fear of failure is related to burnout and psychological stress in athletes and that this association is mainly associated with the individual-oriented dimensions of fear of failure.